By whose rules, for whose needs? The power of elites, livelihood implications and potential for resistance in two Nepalese community forest user groups - Harrer, Constantin (2017)
The Nepalese community forestry program entitles user groups to autonomously manage their forest within the confines of an officially approved operational plan. While widely considered a conservation success, recent discourses on elite capture, professionalization and recentralization question the program’s anticipated social outcomes. This article bridges and exemplifies these discourses by exploring power relationships between forest users, executive committees and forest officials as associated with livelihood impacts and resistance. Findings are based on qualitative interview studies in two forest user groups. Results indicate that operational plans have little practical relevance for forest use. While access for subsistence purposes is largely unlimited, timber is restricted by an increasingly assertive forest administration in cooperation with local elites. This adversely affects those in urgent need for timber such as earthquake victims. Nevertheless, prevailing tacit acceptance of techno-bureaucratic authority allows this coalition to monopolize control over communication, decision-making and resources, and to silence criticism. Resistance has accordingly remained limited but has manifested itself in an anonymous formal complaint and increasing resentment. In conclusion, this study highlights how stakeholders’ access to valuable forest resources and related decision-making rests upon unequal power rather than formal rights. A precondition for change is for a majority to become aware of their rights and to challenge inequality. This process could be facilitated by independent external actors.